Pengaruh Sertifikasi Halal Terhadap Kepercayaan Konsumen Produk Kuliner di Kabupaten Bone - Nuraidah Nuraidah (INDO PUBLISHING, 2026)
This study aims to determine the effect of halal certification on consumer trust in culinary products in Bone Regency. Halal certification has evolved into a symbol of quality, safety, and product integrity, especially in regions with a Muslim-majority population. This study utilized a quantitative approach, with data collected through questionnaires distributed to 100 culinary consumers in Bone Regency. The sampling technique applied was accidental sampling, while the data analysis was performed using simple linear regression with the assistance of SPSS software. The results indicated that halal certification has a significant and positive effect on consumer trust in culinary products within Bone Regency. The existence of the halal label provides psychological reassurance and spiritual certainty for consumers, thereby increasing their confidence in consuming local culinary products. This study recommends that the local government and culinary MSMEs in Bone Regency continue to synergize in accelerating halal certification programs to strengthen the regional economy and consumer protection.